Fibroblast PI3K/AKT signaling and extracellular matrix homeostasis: mechanisms, targets, and delivery challenges - Fang, Chunyun; Zeng, Zitao; Ni, Bin; Wen, Xiaochun; Fang, Zhipeng; Zou, Junrong; Zhang, Guoxi (Frontiers in Cell and Developmental Biology, 2025)
The extracellular matrix (ECM) is essential for tissue homeostasis, ensuring structural stability, facilitating cell-cell communication, and tightly controlling key cellular processes, including proliferation, differentiation, and migration. Numerous cell types and signalling cascades direct ECM turnover; chief among them, the phosphatidyl-inositol-3-kinase (PI3K)/AKT (protein kinase B, PKB) axis remains intensively studied in fibroblasts. Recent evidence indicates that the integration of extracellular cues with intracellular mediators in fibroblasts can modulate the impact of the PI3K/AKT pathway on the ECM. This process is intricately linked to critical fibroblast functions such as metabolic reprogramming, autophagy, apoptosis, and stress responses, ultimately shaping outcomes in fibrotic diseases, wound healing, tissue remodelling, and pathological scar formation. Whereas conventional reviews centre on site-restricted subsets in single disorders, we integrate multi-tissue insights to chart PI3K/AKT signalling across heterogeneous fibroblast populations, taxonomising their sources into a unifying framework that confronts heterogeneity and accelerates precision therapeutic design.